ANALYSIS OF COLLAGEN PRODUCTION IN HYPERTROPHIC CARDIAC TISSUE OF RATS TREATED WITH L-NAME AND L-ARGININE BY IMAGE PROCESSING - Vanessa Oliveira Colombo Marson; Márcia Aparecida Silva Bissaco; Luciano Ramos; Silvia Cristina Martini Rodrigues; Romildo Torres Da Silva; Fernando Francisco Pazello Mafra; Michel Monteiro Macedo; Patrícia Sardinha Leonardo Lopes Martins; Rodrigo Alvaro Brandão Lopes Martins (Revista UniVap, 2019)
We analyzed the production of collagen in the heart of hypertensive rats induced by L-name. Methods: Cardiac imaging of 5 groups: NT, hypertension induced by L-name, L-name and 10 mg L-arginine, L-name and 30 mg L-arginine and L-name and 100 mg L-arginine. Quantification of COL by histology with picrosirius CFC_Image v. 2.0. Calibration of the software by selecting values of hue, saturation and HSI intensity in the reference image, use of the software in the images used. Results: The images did not present statistical differences in any of the HSI sets, indicating that the calibration of the software is valid for the study. Doses greater than 30 mg of L-arginine showed a greater reduction in the collagen areas, indicating a greater protection of the cardiac structures in hypertension. Conclusion: CFC_Image v. 2.0. The accuracy demonstrated in the quantification of COL, L-arginine supplementation promoted protective effects in murine models of hypertension.